PEMANFAATAN PEKARANGAN DALAM PENINGKATAN GIZI KELUARGA PADA MASA PANDEMI COVID-19 DI KAMPUNG TOMPEYAN YOGYAKARTA - Nur Aisyah Rachman; Silviana Nafisa Yunitasari; Salsabilla Salsabilla; Azzukruf Nisa Adira; Dania Rahmawati; Sabrina Rizkiananda; Adib Suyanto; Siti Hani Istiqomah; Sri Muryani (JPS : Jurnal Pengabdian Serulingmas, 2022)
Health development aims to increase awareness, willingness and ability to live healthy for every human being in order to realize the degree of public health. Family Nutrition Improvement Efforts are one of the activities that can be carried out by families to improve nutrition for family members. Utilization of the yard does not only require a large area of land, the use of wall polybags is one solution if the house does not have a yard. Tompeyan Village is an ecotourism and has the title as a Vegetable Village which is located in the middle of the city of Yogyakarta. This Family Nutrition Improvement Business activity aims to change people's behavior and habits to consume balanced nutritious food. The methods used are community nutrition counseling, nutrition services at posyandu and use of yards to improve family nutrition. Based on the results of planting pakcoy, lettuce, and celery that these vegetables can be harvested within 4 weeks. The results of these vegetable plantings can be consumed or sold by residents of RW 03. The conclusion of the activities carried out is to help foster the enthusiasm of the residents of Kampung Tompeyan to re-green the surrounding environment in an effort to improve family nutrition and can maintain the title of Kampung Tompeyan as a Vegetable Village.